Justiça de transição e ministério público: o papel do ministério público federal brasileiro no debate do controle de convencionalidade sobre a lei de anistia - Gonçalves, Heloísa Clara Araújo Rocha (2017)
The purpose of this research is to investigate the proposal for the Brazilian transitional justice process through the conventionality control of the Inter-American Court of Human Rights, which has been articulated, internally, from the persistent performance of members of the Federal Public Ministry. It is examined that in 1979 was published the Law 6.683 (Amnesty Law), which pardoned the political and related crimes executed in the interim of the military dictatorship. On November 24, 2010, the Inter- American Court of Human Rights, when analyzing the case of "Gomes Lund and others versus Brazil," decided that the Amnesty Law can not be valid, since it violates human rights precepts. Thus, it imposed on the Federative Republic of Brazil the obligation to investigate, prosecute, and, if appropriate, punish those responsible. This ruling was not followed, although the Brazilian State recognized the mandatory jurisdiction of this Court since 1998. It is analyzed that, unlike the Judiciary of the other South American countries, the Brazilian Judiciary does not apply the conventionality control that The Inter-American Court determines. Thus, the process of transitional justice for democracy remains impaired. Notwithstanding the difficulties imposed, the Federal Public Ministry, aiming to promote the rights to truth, memory and justice, and, consequently, to strengthen Brazilian citizenship and democracy, has been seeking, based on the conventionality control, to hold State agents responsible for human rights violations in the dictatorial period. The research on the subject is justified because it is socially relevant since it interprets the amnesty law in light of the American Convention on Human Rights, allowing the exercise of the conventionality control, it is a significant issue for the implementation of transitional justice and, therefore, for the development of democracy. The research in focus is theoretical-discursive, essentially bibliographical and jurisprudential, and makes use of the documental analysis method. Regarding the research technique, the technique of Indirect Documentation was used, since it is a bibliographical research. In relation to data analysis, techniques common to documentary research were used. At the outset, a study will be made of transitional justice, observing its concept and its process in some States, as comparative to the Brazilian. Subsequently, the historical context of the Brazilian military dictatorship will be briefly analyzed. Next, it will examine the conventionality control as a transitional justice instrument in Latin America. The research will end with a reflective study on the performance of the Federal Public Ministry in view of the need to promote the rights to truth, memory and justice in the Federative Republic of Brazil.